PREVALENCE AND DETERMINANTS OF DEPRESSION AMONG AMPUTEES IN QUETTA REGION - Khan , Abdul Baqi; Zia, Qasim; Khan, Muhammad Ilyas; Humaira; Kant, Sara Bashir; Qadeer , Asma Abdul; Jawad Abbasi, Mudassar Mushtaq (Journal of Ayub Medical College Abbottabad, 2024)
Background: Depression is increasingly diagnosed in the general population today. The loss of a limb through amputation, which can result in disfigurement, may also contribute to the development of depression despite pre-operative counselling. Understanding the factors associated with depression in individuals with limb amputation is important to effectively identify and manage this psychological condition. The objective of this study was to identify the factors associated with depression in individuals who have undergone limb amputation. Methods: A descriptive cross-sectional study was conducted in Quetta City from May to July 2018. Data were collected using a structured, respondent-cantered questionnaire based on the Hospital Anxiety and Depression Scale (HADS). Results: Females were more affected as 5 out of 7 (71.42%) were depressed compared to 32 out of 47 (68%) males. The study found a statistically significant association between depression and marital status (p-value of 0.047) as well as amputation (p-value of 0.039). These results suggest that both sociodemographic factors, such as marital status, and the experience of amputation are associated with the development of depression in individuals with limb amputation. Conclusion: Amputation is significantly associated with the level of depression among amputees, and sociodemographic factors, such as marital status, also play a role in the development of depression. Therefore, it is recommended to conduct yearly screenings for depression following an amputation to effectively identify and manage this psychological condition. Further research and interventions are needed to address the mental health needs of individuals with limb amputation and implement strategies for depression prevention and management in this population.